MODELING AND STATIC MODAL ANALYSIS OF GANTRY CRANE USING VARIOUS MATERIALS (International Journal of Food and Nutritional Sciences, 2021)
A crane is lifting machinery, discontinuous movement aimed at raising and distributing loads in space, suspended from a hook. Cranes available in the market are grinder travelling crane, overhead travelling crane, jib cranes, wire rope hoist, and gantry cranes. The Gantry cranes are one of the most important mechanical components in the heavy weight lifting and loading in to cargos, into trains, in to heavy truck vehicles, etc. Different types of gantry cranes available in the industries are container cranes, workstation gantry cranes (or) light weight mobile gantry cranes and semi gantry cranes. These vase verity of gantry cranes are differed based on the tonnages and area to be covered for lifting and moving the weights. The workstation gantry crane is the most economical solution in all those places where it is desired or civil works or expensive fixed mount metal structures, and where necessary make loading (or) unloading on a regular basis and at points different. In our project, first, three dimensional geometry of the workstation gantry crane is built in, SOLIDWORKS. Then analysis of I-section beam, the part which is used to carry the loads in Gantry crane, is carried out by using finite element method in ANSYS software for different loads Apply on I section, clamp, hook and at different positions. Using materials in this project structural steel, 34CrMo4Chrome steel, carbon steel 1020, AISI 4130. We estimate the load bearing capacity of I-section beam by placing the loads at different positions i.e. (from left end of I-section, 1stposition is 1300mm, 2ndposition is 4300mm and 3rd position is 5300mm) and by observing von-missies stresses, Shear stress, and deflections generated from static analysis in ANSYS 14.5. finally concluded the suitable material on these 4 materials and which position and find out the deformations in different frequencies by using modal analysis